Acuicultura multitrófica integrada (imta) aplicada al cultivo de especies de interés acuícola en un sistema híbrido (zwd-raz-symbiotic). - Honores Salcedo, Erick Jefferson; Avila Armijos, Lenin Mauricio (Machala : Universidad Técnica de Machala, 2023)
The objective of the research work was to determine the feasibility and sustainability of applying an Integrated Multi-Trophic Aquaculture (IMTA) system in a hybrid system (ZWD-RAS-SYMBITIC) for managing aquaculture species of interest, including red tilapia (Oreochromis sp.), chame (Dormitator latifrons), and Pacific white shrimp (Litopenaeus vannamei), carried out over a 14-week cultivation period. The growth rate and survival of the three aquaculture species in the IMTA system within a hybrid system were described. The initial weights were 320 ± 0,1 g for chame, 183.6 ± 0.1 g for red tilapia, and 0,1 ± 0,1 g for shrimp. Shrimp were fed according to a feeding schedule tailored to their nutritional needs, while fish were fed at 1,5% of the fish biomass to encourage them to feed on suspended solids. The results indicate that the weight gain was more significant in fish compared to shrimp. Additionally, the survival rate in red tilapia was higher compared to what was observed in chame and shrimp, with values of 93,33%, 92,31%, and 82,67%, respectively. The effect of the IMTA system in a hybrid system yielded positive results, as ammonia levels decreased from initial values of 1 ± 0,25 ppm to favorable levels of 0 ppm for the cultivation of these aquaculture species. The system also maintained a uniform water flow in all tanks, keeping salinity consistent at 7460 ± 1,0 ppm, making the adaptability of the species to this technique positive. These results demonstrate that these three species are suitable for cultivation in the IMTA system within a hybrid system. Key water quality parameters such as temperature, pH, TDS, salinity, and TAN remained within recommended limits for these species, ensuring safe nitrite levels. This effective control of parameters indicates optimal waste management and nutrient conversion. Although there were no significant differences in growth between chame and tilapia, there was a reduction in total ammonia levels and control of NH3, suggesting that tilapia contributed to reducing suspended solids. These findings support the applicability of IMTA in a hybrid system for key aquaculture species. The technology proved to be effective in managing environmental conditions and waste, offering significant potential for advancing sustainable and profitable aquaculture. The results open up new possibilities for future research and practical.
El objetivo del trabajo de investigación fue determinar la viabilidad y sostenibilidad de la aplicación de un sistema de Acuicultura Multitrófica Integrada (IMTA) en un sistema hibrido (ZWD-RAS-SYMBITIC) en el manejo de especies de interés acuícola, tilapia roja (Oreochromis sp.), chame (Dormitator latifrons) y camarón blanco del pacifico (Litopenaeus vannamei), ejecutado en 14 semanas de cultivo. Se describió la tasa de crecimiento y supervivencia de las tres especies de interés acuícola bajo el sistema de IMTA en un sistema hibrido, en donde los pesos iniciales fueron en chame 320 ± 0,1 g, 183,6 ± 0,1 g en tilapia roja y 0,1 ± 0,1 g para camarones. Los camarones fueron alimentados acorde a la tabla de alimentación elaborada acorde a sus necesidades nutricionales por otro lado los peces fueron alimentados acorde al 1,5 % de la biomasa de peces, con el fin de estimular a los peces a que se alimenten de los sólidos en suspensión. Los resultados muestran que el aumento de peso fue más significativo en peces en comparación al camarón, además la supervivencia en tilapia fue mayor en comparación a lo obtenido en chame y camarón, siendo estos valores 93,33%, 92,31% y 82,67% respectivamente. El efecto del sistema IMTA en un sistema hibrido los resultados fueron positivos, debido a que los niveles de amonio disminuyeron, teniendo valores iniciales de 1 ± 0,25 ppm hasta bajar a niveles de 0 ppm favorables para el cultivo de estas especies de interés acuícola, además el sistema mantuvo el flujo homogéneo de agua en todos los tanques manteniéndose la salinidad uniforme de 7460 ± 1,0 ppm haciendo que la adaptabilidad de las especies a esta técnica sea positiva. Estos resultados demuestran que estas tres especies son idóneas para ser cultivas bajo el sistema IMTA en un sistema hibrido. Los parámetros clave de calidad del agua como son la temperatura, pH, TDS, salinidad y TAN se mantuvieron dentro de los límites recomendados para estas especies, asegurándose niveles seguros de nitrito. Este control efectivo de los parámetros evidencia una óptima gestión de desechos y conversión de nutrientes, aunque el crecimiento entre chame y tilapia no mostró diferencias significativas, se registró una reducción en los niveles del amonio total y control del NH3, lo cual sugiere que la tilapia contribuyó a disminuir los sólidos en suspensión. Estos hallazgos respaldan la aplicabilidad de la IMTA en un sistema híbrido para especies acuícolas clave. La tecnología demostró ser eficaz en la gestión de condiciones ambientales y desechos, y presenta un potencial significativo para avanzar en la acuicultura sostenible y rentable. Los resultados abren nuevas posibilidades para futuras investigaciones y aplicaciones prácticas en distintos contextos acuícolas.
Keywords: ACUICULTURA MULTITROFICA; INTEGRADA; DORMITATOR LATIFRONS; OREOCHROMIS SP